Shaping success through creative failure: A historical sensemaking analysis of the computerisation of the UK financial market. Issue 1 (2nd January 2022) - Gasparin, Marta; Green, William; Schinckus, Christophe
Abstract: This article draws on the concept of sensemaking and sensegiving to examine how the failure of a project, TAURUS, influenced the successful development of an innovative security settlement system, CREST, which has shaped the computerisation of the wholesale UK financial industry. We use a historiographic interpretative approach to analyse publicly available documents, via three theoretical constructs that have emerged from combining business history and organisational studies literature. First, we define historical sensegiving as the ability to shape contextually the way others make sense of complex historical situations. Second, we establish the sensemaking of failure, which is the ability to make sense of failure in a historical context. Finally, we find that historical enactment supports the creation of structures and events by bracketing them in a historical context. We coin the term 'creative failure' to characterise how failure can be reimagined as a route to creative success through a sensemaking process.